Solve for y 2(y-3)=4y+6

Math
2(y-3)=4y+6
Simplify 2(y-3).
Tap for more steps…
Apply the distributive property.
2y+2⋅-3=4y+6
Multiply 2 by -3.
2y-6=4y+6
2y-6=4y+6
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 4y from both sides of the equation.
2y-6-4y=6
Subtract 4y from 2y.
-2y-6=6
-2y-6=6
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 6 to both sides of the equation.
-2y=6+6
Add 6 and 6.
-2y=12
-2y=12
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=12 by -2.
-2y-2=12-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=12-2
Divide y by 1.
y=12-2
y=12-2
Divide 12 by -2.
y=-6
y=-6
Solve for y 2(y-3)=4y+6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top